The systemic lupus erythematosus travel burden survey: baseline data among a South Carolina cohort. (December 2016) - Williams, Edith; Ortiz, Kasim; Zhang, Jiajia; Zhou, Jie; Kamen, Diane
Abstract Background Many studies on the impact of systemic lupus erythematosus or lupus have identified patient travel costs as being problematic. We administered a survey that examined the impact of self-rated travel burden on lupus patients. The systemic lupus erythematosus travel burden survey included 41 patients enrolled in the systemic lupus erythematosus database project at the Medical University of South Carolina. Results Most participants reported that travel caused medications to be discontinued or appointments to be missed. In unadjusted logistic regressions of the relationship between these outcomes and medical travel burden, both distance to rheumatologists and time to lupus medical care were significant. Conclusions Our findings suggest that more research is needed to examine the influence of travel burden among this population, but data from this report could help to inform physicians, academic researchers, and other health professionals in South Carolina and other areas with significant rural populations on how travel burden may impact patients receiving care for lupus and provide an opportunity for the development of interventions aimed at assisting lupus patients with management of stressors related to travel burden.